Digestibilidade In Vitro/Gás de Volumosos Exclusivos ou Combinados Avaliados pelo Resíduo Remanescente da Digestão da Matéria Seca e Produção de Gás - De Campos, Fábio Prudêncio [UNESP]; Sampaio, Alexandre Amstalden Moraes [UNESP]; De Vieira, Paulo Figueiredo [UNESP]; Bose, Max Lázaro Vieira (My University, 2001)
The in vitro/gas dry matter (DM) digestibility of four roughages, mixed or not, in proportion of 50% in the DM were evaluated. Samples of 100 mg by treatment, in triplicate, in 48 h of digestion were incubated. The DM digestibilities and gas production were: sugar cane = 60.6%, 17.3 mL; sugar cane + corn silage = 63.9%, 19.6 mL; sugar cane + elephantgrass of 60 days = 60.5%, 16.9 mL; sugar cane + elephantgrass of 180 days = 48.6%, 14.1 mL; corn silage = 66.3%, 19.4mL; corn silage + elephantgrass of 60 days = 62.1 %, 16.7 mL; corn silage + elephantgrass of 180 days = 52.7%, 15.8 mL; elephantgrass of 60 days = 61.5%, 16.9 mL; elephantgrass of 180 days = 34.6%, 11.7 mL. It was verified that the association of these roughages can, in some cases, reduce the DM digestibility of those roughages of better quality.
Evaluation of the In vitro/Gas Digestibility of Several Mixtures of Roughages by Digestion Residue of Dry Matter and Gas Production
Keywords: ADF; Corn silage; Elephantgrass; NDF; Sugar cane